The HAND1 frameshift A126FS mutation does not cause hypoplastic left heart syndrome in mice. Issue 14 (31st August 2017) - Firulli, Beth A; Toolan, Kevin P; Harkin, Jade; Millar, Hannah; Pineda, Santiago; Firulli, Anthony B
Abstract: Aims: To test if a human Hand1 frame shift mutation identified in human samples is causative of hypoplastic left heart syndrome (HLHS). Methods and results: HLHS is a poorly understood single ventricle congenital heart defect that affects two to three infants in every 10 000 live births. The aetiologies of HLHS are largely unknown. The basic helix–loop–helix transcription factor HAND1 is required for normal heart development. Interrogation of HAND1 sequence from fixed HLHS tissues identified a somatic frame-shift mutation at Alanine 126 (NP_004812.1 p.Ala126Profs13X defined as Hand1 A126fs ). Hand1 A126fs creates a truncated HAND1 protein that predictively functions as dominant negative. To determine if this mutation is causative of HLHS, we engineered a conditional Hand1 A126fs mouse allele. Activation of this allele with Nkx2.5 Cre results in E14.5 lethality accompanied by cardiac outflow tract and intraventricular septum abnormalities. Using αMHC-Cre or Mef2CAHF-Cre to activate Hand1 A126fs results in reduced phenotype and limited viability. Left ventricles of Hand1 A126FS mutant mice are not hypoplastic. Conclusions: Somatically acquired Hand1 A126FS mutation is not causative of HLHS. Hand1 A126FS mutation does exhibit embryonic lethal cardiac defects that reflect a dominant negative function supporting the critical role of Hand1 in cardiogenesis.